Capote [videorecording (DVD)] / directed by Bennett Miller. - Hoffman, Philip Seymour, 1967-2014; Collins, Clifton, Jr; Keener, Catherine (MPI Media Group, 2025)
Famed author Truman Capote befriends two murderers while researching his celebrated book, 'In Cold Blood,' and finds himself changed to the core.